Customer Satisfaction: Service Quality or Product Quality (Case Study at Fast Food Restaurant in Jabodetabek) - Yudhy Kristiawan; Hartoyo Hartoyo; Budi Suharjo (Binus Business Review, 2021)
Along with the increasing number of fast food restaurant (FFR), the level of competition has also increased. Business owners and managers of FFR are required to provide quality services and products to maintain their existence. Product and service quality and customer satisfaction have a close relationship with company profits. Customer satisfaction is determined by customers’ perceptions regarding product or service performance to meet customer expectations. The research aimed to determine the factors that influenced customer satisfaction of the FFR. The research was conducted in FFR in Jabodetabek using a descriptive approach with survey methods and convenience sampling techniques. Using the Structural Equation Model (SEM), the researchers analyzed several factors that influenced customer satisfaction: service and product quality. The results illustrate that service quality affects customer satisfaction. Satisfied customers will revisit the FFR. However, product quality has no direct effect on customer satisfaction. To improve customer satisfaction, the management of FFR must pay attention to the attributes that contribute greatly but receive low ratings from customers. It consists of the coolness of the room when customers eat and greetings from officers when customers leave the restaurant. Owners and managers of FFR are required to provide service and product quality to maintain their existence.